2023
DOI: 10.1002/ccr3.6937
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum adrenalectomy for pheochromocytoma presenting in pregnancy: A case report

Abstract: Pheochromocytoma is one of the rare causes of hypertension in pregnancy, occurring in one in every 50,000 pregnancies. The aim of this case report is to describe an atypical presentation of pheochromocytoma at 35 weeks gestation, where it presented with right flank pain and seizures, its preoperative medical optimization, and intrapartum concurrent surgical management. It also discusses various clinical presentations of pheochromocytoma in pregnancy, appropriate laboratory and radiological investigations, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…A systematic review by Bancos et al [ 4 ] concluded that severe maternal complications and maternal death occurred in 7% of pregnancies with untreated PPGL. The main causes of maternal mortality include dysrhythmias, cerebrovascular incidents, and pulmonary edema [ 5 ]. The fetal mortality rate has been estimated at 26% in undiagnosed PPGL and 11% in diagnosed cases [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A systematic review by Bancos et al [ 4 ] concluded that severe maternal complications and maternal death occurred in 7% of pregnancies with untreated PPGL. The main causes of maternal mortality include dysrhythmias, cerebrovascular incidents, and pulmonary edema [ 5 ]. The fetal mortality rate has been estimated at 26% in undiagnosed PPGL and 11% in diagnosed cases [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing PPGL in pregnancy is challenged by the low incidence of classic symptoms, such as paroxysmal headaches, diaphoresis, palpitations, and tachycardia [ 1 , 5 ]. Symptoms may appear for the first time during pregnancy or worsen during pregnancy, because of increased vascularity of the tumor and mechanical factors, such as pressure from the enlarging uterus, stimulating catecholamine secretion [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations